Factors Affecting Dynamics of Fish Processing Group in Cirebon Regency - Suheimi, Dedy; Fatchiya, Anna; Harijati, Sri (Jurnal Penyuluhan, 2019)
Traditional processing of fish has a variety of problems. Various problems can be solved through the group on the condition that the group is dynamic. The more dynamic groups make it easier to achieve group goals. This study aims to identify the dynamics of fish processing groups in Kabupaten Cirebon and to analyze factors influencing group dynamics. The research approach is quantitative by survey method and using questionnaire as data gathering tool. The sample in this research is the fish processing which is in twelve groups of fish processing from three districs in Cirebon Regency with the number of samples are 78 fish processor. The data were gathered April 2018. Data were analysed using Statistical Product and Service Solution (SPSS) 24 for descriptive and Partial Least Square (PLS) 3 for inferential statistic. The results showed that the dynamics of the fish processing group in Cirebon Regency are in the high category. From the eight elements of group dynamics there is only one that is in the low category, that is pressure. So, groups are active in interacting to achieve group goals. Group dynamics are influenced significantly and positively by internal and external factors. Internal factors that affect group dynamics are cosmopolitan, long become members and group motivation. External factors that influence group dynamics are the availability of information, the role of extension worker, the role of government and the availability of raw materials. Group dynamics are reflected by structure, coaching and development, atmosphere and effectiveness.